The Donkey in the Narrative Culture and Changing Sociohistorical Epistemology Osel v pripovedni kulturi in spreminjajoči se družbenozgodovinski epistemologiji - Monika Kropej Telban (Studia Mythologica Slavica, 2018)
This article analyses folklore and narrative tradition about donkeys through the prism of ecological paradigm. It explores the impact of the changing philosophy, stereotypes, and peoples’ attitudes towards animals, the donkey in particular. Researched are also changing aspects in the donkey breeding and narrative culture which was for a long time oriented towards speciesism and anthropocentrism, and is now turning towards ecocentric philosophy, which is part of the newly emerging discipline of zoofolkloristics. This ontological shift is projected on the different perceptions of animals in folk literature, language, and everyday life.